تأثير إضافة فيتامين E والسيلينوم ودرجة الحفظ (4 م⁰) على حركية وحيوية نطاف الديك البلدي - جبور, زهير; حميشة, محسن; ملحم, نهال (Latakia University Journal -Biological Sciences Series, 2018)
أجري هذا البحث بهدف دراسة تأثير إضافة فيتامين E والسيلينوم على حركية وحيوية الحيوانات المنوية للديك السوري عند الحفظ على الدرجة +4 م⁰ لمدة 24 و48 ساعة. أظهرت النتائج أن إضافة فيتامين E، وفيتامين E مع السيلينوم حسنت حيوية الحيوانات المنوية وحركتها، لكن الحركة الاهتزازية انخفضت خلال 24 و48 ساعة. كما أظهرت النتائج أن التركيز (5ملغ E +0.6 ملغ Se (، أعطى أعلى قيمة لحيوية الحيوانات المنوية وحركتها السريعة والبطيئة، إذ بلغت هذه الزيادة (17.79%)، (10.65 %)، (8.28%) خلال 24 ساعة على التوالي، و (19.29%)، (10.06%)، (10.37%) خلال 48 ساعة على التوالي، في حين أن التركيز (10ملغ E +0.6 Se) أعطى أدنى قيم للمؤشرات التي تم ذكرها، بينما أعطى التركيز الأول أدنى القيم والثاني أعلى القيم للحركة الاهتزازية. أظهر التحليل الاحصائي اختلافاً كبيراً بين المؤشرات المدروسة (P<0.001). In this study are evaluated the effects of addition of vitamin E and Selenium on the sperm motility and vitality of Syrian rooster, at storing at 4 C⁰ for 24 and 48 hours. The Results showed that the addition of both vitamin E and E with Selenium improved the sperm vitality and movement, but the vibration movement was decreased during 24 and 48 hours. Our results also showed that the concentration of (5mg E+0.6mg Se) gave the highest value of sperm vitality, rapid and slow movement with 17.79%, 10.65%, 8. 28% respectively for 24 hours, and 19.29%, 10.06% 10.37% respectively for 48 hours. Whereas the concentration of (10 mgE+0.6 Se) gave the lowest values of mentionned parameters. Contrarily, the first concentration gave the lowest and the second the highest values of the vibration movement. Finally, the statistical analysis (p<0.001) showed a significant difference between studied parameters.